Multiplexer Based Multiplications for Signal Processing Applications - Pankaj Kumar Sinha; Preetha Sharan (Institute of Advanced Engineering and Science, 2018)
In signal processing, Filter is a device that removes the unwanted signals. In any electronic circuits, Filters are widely used in the fundamental hands on tool. The basic function of the filter is to selectively allow the desired signal to pass through and /or control the undesired signal based on the frequency. A signal processing filter satisfies a set of requirements which are realization and improvement of the filter. A filter system consists of an analog to digital converter is used to sample the input signal, traced by a microprocessor and some components such as memory to store the data and filter coefficients. Filters can easily be designed to be “linear phase” and it is easy to implement. In this paper, the birecoder multiplier (BM) is designed in terms of VLSI design environment. The proposed multiplier is implemented by using VHDL language and Xilinx ISE for synthesis. The multiplier is mainly used for image processing applications as well as signal processing applications.